Minerales Pesados como Indicadores de Ambiente Tectonico en Arenas de la Plataforma Argentina entre los Paralelos 39º Y 43º Sur y El Golfo San Matías - SPAGNUOLO, JORGE OSVALDO; GELÓS, EDGARDO MARTÍN (Pesquisas em Geociências, 1998)
Suites of heavy minerals of an Argentine continental shelf sector and San Matías Gulf were studied. The preponderance of the mafic suite was characterized by the abundance of clinopiroxenes (green augites) and ortopiroxenes (hyperstenes). In scarce proportion green hornblende, brown hornblende, lamprobolite and olivine are present. The suite derived from metamorphic rocks is always in percentages lower than 10% and is represented by epidote and garnet. The suite derived from metamorphic-granitic complex appears in form of traces, integrated by zircon, tourmaline, sillimanite and andalousite. Based on heavy minerals suites it was established that the sands correspond to a volcaniclastic paragenesis. They would come from active margins related to volcanic arches. The origin of the sediment would be related to the Tertiary volcanism of the “Andes”. The sediment resting area corresponds to a passive margin. The compositional differences between the continental shelf (platform) and continental sands respond to the proximity to different sources of contribution. The different etching grain surface that heavy minerals present could be attributed to several causes, among them intrastratal solution and action of sorting and mechanical abrasion in beach environment bring out.